Algorithm for optimal correction of train traffic schedule - Mišauskaitė, Indrė; Bagdonas, Vaclovas (Transport, 2006)
The article analyses the problem of train traffic schedule optimal addition according to minimum overall expenditure criteria. The task is to analyze optimal insertion of an additional train track into already made schedule. The methodology is all‐right applicable for ad hoc requests submission. Handling importance of ad hoc requests is emphasized in EU directive 2001/14/EB. The task can be solved applying Monte‐Carlo, genetic algorithms, variants reselection methods or methods of the shortest (according to waste) way in graphs. All these methods are equally exact and can be implemented in modern computers with short enough time consumption.First Published Online: 27 Oct 2010